Correlation between interleukin-6 expression in post-mortem core liver biopsy and degree of liver injury in patients with fatal COVID-19 - Maimunah, Ummi; Maharani, Andi RK.; Soegiarto, Gatot; Rahniayu, Alphania; Gunawan, Vania A.; Wiratama, Priangga A.; Djuanda, Stephanie N.; Supriadi, Supriadi; Marhana, Isnin A.; Semedi, Bambang P.; Lefi, Achmad; Kusumastuti, Etty H.; Suyanto, Edi; Lilihata, Jilientasia G.; Anggoro, Adhitri; Rinjani, Lalu GP.; Rosyid, Alfian N.; Wahyu, Dwi; Fauziah, Dyah; Rahaju, Anny S.; Kurniasari, Nila; Ariani, Grace; Nugroho, Gilang MS.; Yandi, I KR.; Nugraha, Ricardo A. (Narra J, 2023)
Excessive release of interleukin-6 (IL-6) during the progression of coronavirus disease 2019 (COVID-19) induces cytokine storms, resulting in multi-organ damages including liver injury, similar in nature with mechanism of viral hepatitis. Systemic IL-6 has been associated with the incidence of liver injury among COVID-19 patients; however, studies on IL-6 expression in the liver tissue are completely lacking. The aim of this study was to measure the IL-6 expression in the liver tissues and to determine its correlation with the degree of liver injury in fatal COVID-19 patients. Through this first cross-sectional study, IL-6 expression was measured through immunohistochemical staining and the degree of liver injury was identified based on level of serum alanine aminotransferase (ALT). The Spearman correlation test was used to identify the correlation between IL-6 expression and the degree of liver injury. A total of 47 deceased COVID-19 patients were included and IL-6 expression was observed in all post-mortem liver specimens, ranging from mild to strong expression. Liver injury at various degrees (mild to severe) was found in more than half (59.5%) of the cases. The Spearman correlation analysis suggested a statistically insignificant correlation between liver IL-6 expression and the degree of liver injury (r=0.152; p=0.309). In conclusion, even IL-6 expression was observed in all post-mortem liver specimens, there was an insignificant correlation between IL-6 expression in the liver tissue with the degree of liver injury among fatal COVID-19 patients, suggesting that IL-6 was not the only main factor contributing to liver damage in COVID-19 patients.